Content Validity of KIP-K Scholarship Instruments at Higher Education Using Aiken's Coefficient Validity Scale - Sabaruddin, Sabaruddin; Nur, Muhammad; Fadli, M.; Mazlan, Mazlan (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze the KIP-K Scholarship instrument at PTKIN IAIN Langsa while developing non-test instruments (questionnaires). This instrument is used to obtain information about students who apply for KIP-K scholarships. The instrument of content validity is obtained through a quantitative analysis by nine selected experts and a qualitative approach with an expert review of a set of questionnaires that have been arranged. In determining the content validity and reliability level, the experts analyzed a questionnaire quantitatively consisting of 29 items with three components: economic, household, and academic and non-academic students’ achievements. The data from this expert judgment is calculated using the formula Aiken V. While expert reviews are qualitatively similar to suggestions and feedback, they are used to refine constructed items. The result of these students’ economic condition, household, and academic and non-academic achievements was above 0.72 with a significance level of 5%, namely 0.92, 0.96, and 0.96. All of the 29 items are very valid (V > 0.72, V1 > 0.50) and reliable (α = 0,944). The conclusion that each component is closely related indicates information on the feasibility of distributing KIP-K. The instruments embodied at IAIN Langsa have high validity, and the level of reliability is excellent. This instrument can obtain complete information on prospective students who will become KIP-K scholarship recipients in 2022.